2004
DOI: 10.1002/ddr.10356
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacogenetics of antihypertensive treatment

Abstract: Hypertension is a common disorder associated with increased cardiovascular morbidity and mortality. Unfortunately, in the United States, only about one third of those who are aware of their hypertensive status successfully control their blood pressure. One reason for this is the variable and unpredictable response individuals have to pharmacologic treatment. Clinicians often resort to a trial-anderror approach to match patients with effective drug treatment. It is the goal of hypertension pharmacogenetics to a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…Apharmacogenetic study of hypertension is still in its infancy. Other factors that may also significantly affect antihypertensive drug response are age, sex, and diet 71 . Although pharmacogenetics provides opportunities to improve drug therapy outcomes, it may increase the complexity of drug prescribing.…”
Section: Discussionmentioning
confidence: 99%
“…Apharmacogenetic study of hypertension is still in its infancy. Other factors that may also significantly affect antihypertensive drug response are age, sex, and diet 71 . Although pharmacogenetics provides opportunities to improve drug therapy outcomes, it may increase the complexity of drug prescribing.…”
Section: Discussionmentioning
confidence: 99%
“…CES1, carboxylesterase 1; CI, confidence interval investigated the effects of genetic variants on the pharmacodynamics of ACE inhibitors [32][33][34][35]. For example, variants in ACE, angiotensinogen, angiotensin receptor 1 and α-adducin 1 have in some studies been associated with the response to ACE inhibitors [36]. However, different studies have yielded conflicting results and further studies are required to clarify the role of genetic variability in the pharmacokinetics and pharmacodynamics of ACE inhibitors.…”
Section: Discussionmentioning
confidence: 99%
“…Type 1 angiotensin II receptor (AGTR) is encoded by the AGTR1 gene. AGTR1 polymorphisms are found to be associated with blood pressure response to the inhibition of reninangiotensin system (RAS) in the hypertensive population [16,17]. A1166C (rs5186) SNP of AGTR1 may be involved in posttranscriptional modification and angiotensin II receptor-mediated cell signaling [18].…”
Section: Introductionmentioning
confidence: 99%
“…A1166C (rs5186) SNP of AGTR1 may be involved in posttranscriptional modification and angiotensin II receptor-mediated cell signaling [18]. A1166C has been extensively studied in hypertension and is associated with the end-point phenotypes [16,17]. Sun et al, found that in Chinese population, A1166C polymorphism of AGTR1 was associated with antihypertensive response to candesartan, and individuals with AC genotype displayed a significantly reduction in SBP after taking candesartan [19].…”
Section: Introductionmentioning
confidence: 99%